Capital and Interest Once More: II. A Relapse to the Productivity Theory - Bohm-Bawerk, E. (Quarterly Journal of Economics, 1907)
Journal Article Capital and Interest Once More: II. A Relapse to the Productivity Theory Get access E. Böhm-Bawerk E. Böhm-Bawerk Vienna Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 21, Issue 2, February 1907, Pages 247–282, https://doi.org/10.2307/1883433 Published: 01 February 1907